Carbohydrate ligands for endothelial-leukocyte adhesion molecule 1. - Tiemeyer, M (1991)
The acute inflammatory response requires that circulating leukocytes bind to and penetrate the vascular wall to access the site of injury. Several receptors have been implicated in this interaction, including a family of putative carbohydrate-binding proteins. We report here the identification of an endogenous carbohydrate ligand for one of these receptors, endothelial-leukocyte adhesion molecule 1 (ELAM-1). Radiolabeled COS cells transfected with a plasmid containing the cDNA for ELAM-1 were used as probes to screen glycolipids extracted from human leukocytes. COS cells transfected with this plasmid adhered to a subset of sialylated glycolipids resolved on TLC plates or adsorbed on polyvinyl chloride microtiter wells. Adhesion to these glycolipids required calcium but was not inhibited by heparin, chondroitin sulfate, keratan sulfate, or yeast phosphomannan. Monosaccharide composition, linkage analysis, and fast atom bombardment mass spectrometry of the glycolipids indicate that the ligands for ELAM-1 are terminally sialylated lactosylceramides with a variable number of N-acetyllactosamine repeats and at least one fucosylated N-acetylglucosamine residue.